China's Approach to Addressing International Hotspot Issues: Concepts, Principles and Practices - 王帆 (中国国际问题研究：英文版, 2024)
From bystander to participant and further to independent mediator, China is playing an increasingly extensive part in resolving hotspot issues. Building on its traditional culture and diplomatic practice, China has promoted fundamental resolution through temporary solutions of hotspot issues, addressed traditional security issues through non-traditional security cooperation, integrated dispute resolution with regional development, and worked to build regional dialogue and cooperation mechanisms. The approach to addressing hotspot issues enriches the concept of governance, and has been highly recognized by the international community.